Participatory approaches for developing a practical handbook integrating health information for supporting individuals with mild cognitive impairment and their families - Yujiro Kuroda; Aya Goto; Taiki Sugimoto; Kosuke Fujita; Kazuaki Uchida; Nanae Matsumoto; Hiroyuki Shimada; Rei Ohtsuka; Minoru Yamada; Yoshinori Fujiwara; Aya Seike; Madoka Hattori; et al. (Health Expectations)
Abstract Aim This study aimed to develop a patient‐centred handbook that integrates information on lifestyle modifications and psychological support strategies for individuals with mild cognitive impairment (MCI). This article provides a comprehensive record of the development process. Methods We adopted a participatory research model for the methodology, which comprised five phases and involved an interdisciplinary team specializing in dementia and health literacy. Data were initially collected via interviews conducted among patients with MCI (n = 5) and their families (n = 5). Given the study's preliminary nature, depth and richness of the qualitative data were the key concerns for determining the sample size, rather than broad generalizability. We ensured the inclusion of diverse experiences and perspectives by facilitating the creation of patient questions (PQs) that merged scientific evidence with patient perspectives. To enhance the handbook's accessibility and utility, we continuously evaluated the same using patient interviews, health literacy tool assessments and team discussions. This comprehensive approach harmonized scientific knowledge and patient experience, leading to the development of a personalized MCI management guide. Results The handbook comprises nine domains, encompassing 38 selected PQs: MCI, lifestyle, lifestyle‐related diseases, exercise, nutrition, social participation, cognitive training, psychological care and family support. The health literacy handbook was evaluated based on Clear Communication Index scores. The results revealed that 73.7% of the PQs were deemed difficult prerevision, whereas only 5.3% remained challenging postrevision. The formative evaluation underscored the need for more detailed explanations prerevision, whereas postrevision comments focused primarily on editorial suggestions. Conclusion The inclusion of patients' perspectives right from the outset ensured that the handbook met their specific needs. The final version, which reflects all stakeholders' inputs, is now slated for imminent publication. Patient or Public Contribution Patients and the public participated extensively throughout the project, from initial interviews to material evaluation and refinement.